The application of soft systems methodology to supply chain risk managment in small and medium enterprises - Maje, Mpho (My University, 2016)
Supply chain risk management is one of the strategies that assist enterprises in the identification, assessment and control of supply chain risks. With the increased dynamics and complexity of supply chain risks for small and medium enterprises, an innovative approach in analysing these risks is required. The purpose of this research is to assess supply chain risk management in five small and medium enterprise cases using soft systems methodology. The systems thinking approach will assist in the analysis of the dynamics and complexity of supply chain risks for small and medium enterprises. A qualitative approach was utilised to obtain insight into current issues that small and medium enterprises, in the manufacturing sector, face within the supply chain. The results of the application of soft systems methodology on small and medium enterprises for obtaining insight into supply chain risk management for these enterprises proved to be fruitful. The replication logic used in each case, lead to similar results as expected.
A research report submitted to the School of Mechanical, Industrial & Aeronautical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Science in Engineering, 2015